2015
DOI: 10.1089/gtmb.2014.0294
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Produced Anti-Human Leukocyte Antigen Antibodies Relation to Alloimmunity in Patients with Chronic Renal Failure

Abstract: Solid organ transplantation appears to have the strongest HLA alloimmunization effect followed by pregnancy and blood transfusion, especially for class II HLA antigens. Patients who were sensitized by more than one sensitization event have a lower chance to have a solid organ transplantation. In this case, identification of donor-specific antibodies and the results of the cross-match tests play an important role both before and postrenal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…27 In the present study, in accordance with Lopes and associates, 7 we confirmed that a transplant has a high immunizing effect for both HLA class I and II compared with pregnancy and transfusion. Likewise, when we compared the antibody strengths (MFI values), as also reported by several authors, 6,28,29 we confirmed that a transplant, mainly for HLA class II, has a significantly higher antibody strength than pregnancy or transfusion. The presence of anti-HLA antibodies in our patients without any known sensitization event (11.4%) and the clinical significance of such antibodies are not clear.…”
Section: Discussionsupporting
confidence: 87%
“…27 In the present study, in accordance with Lopes and associates, 7 we confirmed that a transplant has a high immunizing effect for both HLA class I and II compared with pregnancy and transfusion. Likewise, when we compared the antibody strengths (MFI values), as also reported by several authors, 6,28,29 we confirmed that a transplant, mainly for HLA class II, has a significantly higher antibody strength than pregnancy or transfusion. The presence of anti-HLA antibodies in our patients without any known sensitization event (11.4%) and the clinical significance of such antibodies are not clear.…”
Section: Discussionsupporting
confidence: 87%
“…Lashley et al [3] found that this rise is probably due to the increase in fetal-maternal cell traffic in the last trimester. In our previous study, we found that the women on the transplant waiting list with only a pregnancy history produced more class II than class I anti-HLA antibodies [7]. Masson et al [2] also had the same results (86% and 62% of class I and class II anti-HLA antibodies, respectively).…”
Section: Discussionmentioning
confidence: 57%
“…Risk factors for HLA sensitization include prior transplantation, blood product transfusion, pregnancy, and ventricular assist device use . Of these risk factors, the strongest is a history of prior transplantation.…”
Section: Hla System An Immunologic Barrier To Transplantationmentioning
confidence: 99%